1982
DOI: 10.1523/jneurosci.02-08-01072.1982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxotremorine on local glucose utilization in the rat cerebral cortex

Abstract: The [14C]2-deoxy-D-glucose technique (Sokoloff, L., M. Reivich, C. Kennedy, M. Des Rosiers, C. Patlak, K. Pettigrew, 0. Sakurada, and M. Shinohara (1977) J. Neurochem. 28: 897-916) was used to examine the effects of central muscarinic stimulation on local cerebral glucose utilization (LCGU) in the cerebral cortex of the unanesthetized rat. Systemic administration of the muscarinic agonist oxotremorine (0X0, 0.1 to 1.0 mg/kg, i.p.) increased LCGU in the neocortex, mesocortex, and paleocortex. In the neocortex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…The effects of scopolamine on LCGU in hippocampal and cortical structures (medial, auditory layer IV, frontal layers IV and V) agree well with the results of Dam et al (1982). Weinberger et al (1979) found a significant decrease in the auditory cortex, similarly noted in the present study in layers IV and V, whereas Dam et al (1982) showed a nonsignificant decreased.…”
Section: Discussionsupporting
confidence: 91%
“…The effects of scopolamine on LCGU in hippocampal and cortical structures (medial, auditory layer IV, frontal layers IV and V) agree well with the results of Dam et al (1982). Weinberger et al (1979) found a significant decrease in the auditory cortex, similarly noted in the present study in layers IV and V, whereas Dam et al (1982) showed a nonsignificant decreased.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this view is the fact that microiontophoretically administered LAC increased firing of cortical neurons and this effect was antagonized by atropine [34]. In addition, animal experiments showed that the administration of muscarinic agonists, such as oxotremorine and arecoline, elevate glucose utilization in the cortex of the rat brain, particularly in the parietal area [35,36].…”
Section: Discussionmentioning
confidence: 71%
“…In vitro, ace tylcholine can regulate neuronal activities through 1996 intracellular signaling processes such as those me diated by adenylate cyclase, phosphoinositide, or phospholipase C (Brown and Brown, 1984;Ash kenazi et al, 1987;Dauphin et al, 1994). It has been shown pharmacologically that acetylcholine effec tively excites cortical neurons (Dam et al, 1982;Sato et al, 1987). Thus, neuronal control by acetyl choline via these mechanisms presumably in creased the neuronal activity and energy demands of neurons, resulting in increased glucose consump tion, which was reflected as the increase in both CMR G lu and hexokinase activity, i. e., k3.…”
Section: Discussionmentioning
confidence: 99%